AB0942 RADIOLOGICAL SACROILIITIS AFTER 18 YEARS OF FOLLOW-UP IN THE POPULATION-BASED NORDIC JUVENILE IDIOPATHIC ARTHRITIS (JIA) COHORT. (June 2019) - Qvarnström, Karin; Glerup, Mia; Rypdal, Veronika; Arnstad, Ellen Dalen; Peltoniemi, Suvi; Ekelund, Maria; Fasth, Anders; Nielsen, Susan; Zak, Marek; Aalto, Kristiina; Nordal, Ellen; Herlin, Troels; et al.
Abstract : Background: A challenge with the present classification of JIA is the evolution of the disease over time. One category that is especially difficult to classify is enthesitis-related JIA (ERA). Objectives: To longitudinally study radiologically diagnosed sacroiliitis (SI) developed during the first 18 years in an aim to gain knowledge about classification challenges posed by the proposed, new classification (Martini A. et al. J Rheumatol. 2018 Oct; Epub ahead of print). Methods: 510 consecutive cases of JIA with disease onset 1997 to 2000 were prospectively included in a Nordic, longitudinal, close to population-based 18-year follow-up study, and 434 (85%) had at least two follow-up visits during disease course. At the 18-year follow-up visit; 329 (76%) attended a clinical visit, and 105 (24%) a telephone interview. The follow-up period was 17.5 ± 1.7 years (mean ± SD) after onset. Mean age of the study participants was 24.0 ± 4.4 years. Clinical data, collected at one, eight and 18 years after disease onset, were evaluated regarding variables for enthesitis/spondylitis-related arthritis compared to the other JIA categories. Results: In 376 participants evaluated for SI, radiology was performed on clinical suspicion, 26 (16 males, 10 females) developed radiologically verified sacroiliitis (rad-SI) during the first 18 years of disease. Age at onset was significantly higher in this group compared to the other participants, median 9.9 (IQR 6.4-12.0) vs. 5.6 (IQR 2.6-9.5) years, (p=0.001). Only 3/26 had rad-SI at eight-year follow-up. Using the ILAR criteria 12/26 with rad-SI were classified as ERA after median 7 (IQR 6-10.2) months, 1/26 as juvenile psoriatic arthritis, 5/26 as undifferentiated JIA because of psoriasis-related variables, the remaining had oligo- or polyarticular arthritis. At 18-year follow-up, 18/26 fulfilled criteria for ERA, 2/26 juvenile psoriatic arthritis, and 3/26 the undifferentiated category because of psoriasis-related variables, 3/26 had polyarticular RF negative or oligoarticular extended disease. Enthesitis, inflammatory back pain and SI joint tenderness were more common with rad-SI (p<0.001; p<0.001; p<0.001), also HLA-B27, 18/26 vs. 62/351 (p<0.001), but not 1 st degree heredity for ankylosing spondylitis. Uveitis developed in 10/26 (38.5%). Two participants developed IBD. Conclusion: The majority of variables involved in the new proposed classification of enthesitis/spondylitis-related JIA were significantly more common during the first 18 years of disease in those that developed rad-SI. Psoriasis-related variables, no longer exclusion criteria for ERA, should be further evaluated as possible inclusion criteria, as well as higher age at onset. Disclosure of Interests: Karin Qvarnström: None declared, Mia Glerup: None declared, Veronika Rypdal: None declared, Ellen Dalen Arnstad: None declared, Suvi Peltoniemi: None declared, Maria Ekelund: None declared, Anders Fasth: None declared, Susan Nielsen: None declared, Marek Zak: None declared, Kristiina Aalto: None declared, Ellen Nordal: None declared, Troels Herlin: None declared, Marite Rygg: None declared, Lillemor Berntson Consultant for: AbbVie, Speakers bureau: AbbVie